An Inquiry Project: A Way to Develop a Meaningful Learning Context La indagación: un camino para desarrollar un contexto significativo de aprendizaje - Norha Esperanza Pineda Torres (Profile: Issues in Teachers' Professional Development)
The main purpose of this article is to share an inquiry experience from EFL (English as a Foreign Language) classes, and the reflection that deals with the practical benefits participants have when they are involved in an inquiry proposal. Firstly, there is an introduction to this inquiry process describing the main question that guided this paper. Secondly, a theoretical framework and the authoring cycle description is presented considering the way the inquiry process took place within my classroom by means of meaningful actions and contexts. Thirdly, a data collection section by some reflective responses regarding participants’ learning during the process of developing the inquiry project; and the analysis of findings are explained with some samples. Finally, there are some pedagogical implications as well as some conclusions. El propósito principal de este artículo es comunicar una experiencia de indagación que desarrolló un grupo de estudiantes de inglés como lengua extranjera. Durante este proceso, los participantes lograron aprender varios aspectos educativos, de los cuales se obtuvieron muchos beneficios y enseñanzas. Este artículo consta de una introducción al tema central y las preguntas que generaron este trabajo. Después de esto, se presentan algunos aspectos teóricos importantes sobre el tema, así como una descripción del proceso significativo de indagación que se aplicó en el contexto de clase. Luego se describen y analizan la información y los datos recogidos durante el estudio. Por último, se presentan algunas implicaciones pedagógicas y conclusiones finales.